The influence of object size on judgments of lateral separation. Issue 1 (2nd January 2016) - Thomson, Robert; Pyke, Aryn; Lacroix, Guy L.
Abstract : The size of a previously experienced object has a significant effect on depth judgments in visually sparse environments. The present research explored whether familiar object size also significantly influences judgments of lateral separation. Experiment 1 required participants to detect changes in lateral separation using a one-shot change detection paradigm with a closer/same/farther forced-choice response. Participants accurately detected changes in lateral separation, although concurrent changes in object size significantly reduced the accuracy of their judgments such that increases (or decreases) in object size caused a relative underestimation (or overestimation) of separation. Experiment 2 replicated these results using a distance reproduction methodology. These results indicate that familiar object size exhibits a significant effect on judgments of lateral separation.